Metacognitive Process of Mathematics Education Students in Solving Calculus Problems on Integral Material - Siti Maslihah; Kartono Kartono; Wardono Wardono; Iqbal Kharisudin (Phenomenon : Jurnal Pendidikan MIPA, 2025)
One of the skills that someone must have if they want to study mathematics and solve mathematical problems is metacognitive ability, namely the ability to control and open their own thinking. This study was conducted on students majoring in mathematics education to determine their metacognitive skills and metacognitive strategies in solving integral calculus problems. The research subjects were taken from the same gender. The results of the study showed that students who use their metacognitive abilities consciously and use more metacognitive strategies can solve more mathematical problems compared to students who have less metacognitive abilities and do not use metacognitive strategies well.